Hubungan antara Persepsi Siswa terhadap Kepribadian Guru dan Jenis Kelamin Siswa dengan Minat Belajar Matematika (Survei studi kasus terhadap siswa/i SMA Tugu Ibu Depok) - Ul'fah Hernaeny (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2011)
Mathematics has an influence and a very large role in discovering and developing Science and Technology. For that, mathematics has priority in education. Student success in learning mathematics can be known from the ability to put that understanding to solve any mathematical problem and other problems in everyday life. Capabilities acquired by students in understanding the lessons in school because no other role of a teacher who is able to provide concepts is easily accepted by students. Personality of a teacher is affecting students' interest in studying mathematics. This study departed from the idea that the perception of students towards mathematics teacher's personality is affecting student interest in learning mathematics, students both male and female students. The purpose of this study, among others, want to know and analyze the relationship between student perceptions of teacher's personality and gender of students with interest in learning math in high school Yaspen Tugu Ibu Depok. As the population in this research determines the entire class X school year 2005/2006, which consists of three classes with 120 people the number of students per class is 40 people. While the sample used is a class X A. Peneltian methods used to analyze the relationship between student perceptions of teacher's personality and gender of students with interest in learning math in high school Yaspen Tugu Ibu Depok method is to use descriptive correlative. The tendency of writers to use it because the method is explained and described the existing conditions of objects as well as coordinating existing objects. After the authors analyze the relationship between student perceptions of teacher's personality and gender of students to the interest in learning mathematics in high school Yaspen Tugu Ibu Depok, ultimately the author can draw the conclusion that there is a very significant and strong between teacher personality and gender of students with interest in learning mathematics.